2022
DOI: 10.1101/2022.12.22.521628
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of cannabis use on immune cell populations and the viral reservoir in people with HIV on suppressive antiretroviral therapy

Abstract: HIV infection remains incurable due to the persistence of a viral reservoir during antiretroviral therapy. Cannabis (CB) use is prevalent amongst people with HIV (PWH), but the impact of CB on the latent HIV reservoir has not been investigated. Peripheral CD4 and CD8 T cells from a cohort of CB-using PWH and a matched cohort of non-users on antiretroviral therapy were evaluated for expression of maturation/activation markers, HIV-specific T cell responses, and the frequency of intact proviral DNA. CB use was a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…These data indicate that cluster membership is highly associated with the overall level of immune activation and exhaustion for the individual. We have previous shown that cannabis use reduces the overall level of immune activation and inflammation in PWH, despite having minimal impact on the size of the HOV reservoir (52). Interestingly, a subset of participants in this study had clinical data regarding cannabis (CB) use.…”
Section: Dimension Reduction Reveals Two Clusters Of Pwh With Distinc...mentioning
confidence: 85%
See 1 more Smart Citation
“…These data indicate that cluster membership is highly associated with the overall level of immune activation and exhaustion for the individual. We have previous shown that cannabis use reduces the overall level of immune activation and inflammation in PWH, despite having minimal impact on the size of the HOV reservoir (52). Interestingly, a subset of participants in this study had clinical data regarding cannabis (CB) use.…”
Section: Dimension Reduction Reveals Two Clusters Of Pwh With Distinc...mentioning
confidence: 85%
“…66 PWH were recruited at Duke University medical center and 49 PWH at UNC Chapel Hill. Peripheral blood was collected and peripheral blood mononuclear cells (PBMCs) were obtained by Ficoll separation, then frozen in 90% fetal bovine serum 10% dimethylsulfoxide (DMSO) (52,59,70,71).…”
Section: Cohort and Sample Collectionmentioning
confidence: 99%